The Association of Alagille Syndrome and Craniosynostosis - Yilmaz, Sanem; Turhan, Tuncer; Mutluer, Saffet; Aydogdu, Sema (Pediatric neurology, 2013)
Alagille syndrome is associated with various ocular abnormalities, including pseudopapilledema or optic disk edema due to increased intracranial pressure. Several mechanisms have been proposed to explain the mechanism of intracranial hypertension in Alagille syndrome. Craniosynostosis is an unusual but significant cause of increased intracranial hypertension in Alagille syndrome. It has recently been demonstrated in animal models that Jagged1 gene in which mutations are responsible for Alagille syndrome may also take part in cranial suture formation. We report a child with Alagille syndrome and craniosynostosis who presented with pruritus, elevated liver enzymes, and suspected increased intracranial pressure.